Substance and Attribute. Western and Islamic Traditions in Dialogue - Legenhausen, Muhammad (Publications of the Austrian Ludwig Wittgenstein Society - New Series (N.S.), 2007)
The aim of this volume is to investigate the topic of Substance and Attribute. The way leading to this aim is a dialogue between Islamic and Western Philosophy. Our project is motivated by the observation that the historical roots of Islamic and of Western Philosophy are very similar. Thus some of the articles in this volume are dedicated to the history of philosophy, in Islamic thinking as well as in Western traditions. But the dialogue between Islamic and Western Philosophy is not only an historical issue, it also has systematic relevance for actual philosophical questions. The topic Substance and Attribute particularly has an important history in both traditions; and it has systematic relevance for the actual ontological debate.